PTH-330 Detection and treatment of liver metastasis from colorectal cancer. (22nd June 2015) - Jones, R; Newton, A; Lisseter, E; Jha, M
Abstract : Introduction: As the principal site of distant spread, the detection and management of liver metastasis is crucial in patients with colorectal cancer. Untreated, the median survival is around 6–12 months. The aim of this study was to assess the way in which colorectal liver secondaries are detected and to assess the outcomes associated with their management. Method: We set up and prospectively maintained a database detailing the clinical and radiological features of all patients with liver metastasis secondary to colorectal cancer in a high-volume unit. For the period 2008–2012, we reviewed the events leading to a diagnosis of liver metastasis, the initial treatment intent and median survival rates. Results: During the study period, 1292 new cases of colorectal cancer were discussed in our multidisciplinary team meeting and of these, 216 had liver metastasis confirmed by computed tomography (CT) scanning. Liver metastasis was noted at the time of the initial diagnosis in 160 patients and metachronous lesions were detected in 56 patients. Metachronous metastases were detected after a median of 12 months (range 3–53). The length of the interval had no bearing on survival. The majority of metachronous liver metastases were detected with scheduled monitoring (41% by carcino-embryonic antigen and 39% on surveillance CT scan) but 16% presented symptomatically. From the time of initial diagnosis, the median survival for the synchronous and metachronous cases was 53 months and 57 months, respectively. 20% of the synchronous and 88% of the metachronous cases were treated with curative intent after the initial diagnosis of colorectal cancer. Of the 216 patients diagnosed with liver metastasis, 50 (23%) were referred to the local hepatobiliary unit for consideration of metastectomy. 11 patients were deemed unresectable and a further eight patients were either unfit or declined resection. Liver resection was undertaken in 9% of the synchronous and 30% of the metachronous cases. From the time of their initial diagnosis, the median survival for the 31 patients who underwent hepatic metastectomy was 53 months; survival was 59 months in the synchronous and 47 months in the metachronous groups. Conclusion: Scheduled colorectal cancer surveillance serves to identify the majority of liver metastases, but history-taking and examination lead on to detection in a significant minority. With appropriate patient selection, resection of both synchronous and metachronous liver secondaries offers a significant survival benefit. Disclosure of interest: None Declared.